SOCIAL HUMANITARIAN TECHNOLOGIES: ROLE IN THE KNOWLEDGE SOCIETY - Онопрієнко, М. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the last decades among the newest technologies picks out an emersion of specific social-humanitarian technologies. The character of these technologies is not enough researched, and there is a considerable confusion in their understanding. There is a contradiction in these technologies: on the one hand they refer to «humanize» technique and technologies, from the other hand, these are technologies of consciousness manipulation. The development of these technologies accomplished on the basis of the newest social humanitarian knowledge